ANALISIS DAN RANCANGAN DI PT HONDA - Sri Alwiyah Silvia; Hendra Riofita (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2024)
The next step is to conduct job analysis after planning human resource needs. "Job analysis is the process of studying and collecting information related to the operation and responsibilities of a particular job" (Flippo, 1989). job analysis literature The science of job analysis studies employment and the process of identifying the prerequisites that need to be met, such as methodical recruitment, appraisal or control, and organization or business. In other words, job analysis is the process of researching, identifying, and designing activities that determine the duties, responsibilities, and types of tasks that must be performed by each job for its personnel. Operational Strength PT Honda has strong operational capabilities, supported by supply chain efficiency, advanced production technology, and skilled human resources. This allows the company to produce high-quality vehicles and innovate continuously.